Electrochemical supercapacitive performance of spray deposited Co3O4 thin film nanostructures. (1st April 2017) - Yadav, Abhijit A.; Chavan, U.J.
Graphical abstract: Highlights: Electrochemical supercapacitive performance of Co3 O4 nanostructures. Porous morphology has been observed from SEM. Highest specific capacitance of 425 Fg −1 for film deposited at 350 °C. Retention of 92.56% specific capacitance after 1000 cycles. Abstract: In this report, we have obtained cobalt oxide (Co3 O4 ) nanostructures at various substrate temperatures by chemical spray pyrolysis using mixed aqueous/organic solvent. The influence of substrate temperature on the film properties has been studied. From X-ray diffraction studies the cubic phase of Co3 O4 is confirmed. SEM shows porous morphology, which is advantageous for supercapacitor applications. Two direct allowed optical transitions are observed. Co3 O4 nanostructures exhibit good electrochemical performance with excellent cycle stability and high specific capacitance of 425 Fg −1 at a scan rate of 5 mVs −1 . Specific capacitance of Co3 O4 films decayed to 7.44% at 1 Ag −1 after 1000 charge/discharge cycling tests in 2 M aqueous KOH electrolyte. The electrochemical impedance spectroscopy study indicates that Co3 O4 nanostructures deposited at 350 °C substrate temperature has better electrochemical properties. The present study is suitable in developing new class of portable energy storage devices.